Custom-built wireless pressure sensing insoles for determining contact-times in 60m maximal sprint running - Kuntze, G.; Pias, M.; Bezodis, I.; Kerwin, D.; Coulouris, G.; Irwin, G. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to evaluate a custom-built wireless pressure sensing insole system for recording ground contact times in sprinting. Despite interest in the foot contact time/running velocity relationship, no study has examined the contact times in a maximal 60 m sprint. Insole data were collected on three athletes during maximal indoor sprint runs. Simultaneous kinematic data for start and maximum velocity phases were recorded with a CODA system to validate insole contact times and determine velocity. Insole derived contact times were accurate to ±4 ms. Preliminary data indicate a usable contact time/velocity relationship. It is anticipated that these data will provide support for the use of wireless technology in sprint performance monitoring, and facilitate novel insights into the contact time/sprint running velocity relationship.